"Like I Have No Choice": A Qualitative Exploration of HIV Diagnosis and Medical Care Experiences While Incarcerated and Their Effects. Issue 2 (3rd April 2019) - Kutnick, Alexandra H.; Leonard, Noelle R.; Gwadz, Marya V.
Abstract: It is estimated that one in six Black and Latino adult persons living with HIV (PLWH) spend time in correctional institutions each year. Yet after release, PLWH of color evidence poor HIV health outcomes across the HIV care continuum. This study, guided by an ecological approach and Critical Race Theory, sought to understand the lived experiences of socioeconomically disadvantaged PLWH of color who received an HIV diagnosis and/or medical care while incarcerated, and the ways in which those experiences influenced engagement in medical care after release. Drawn from a larger study in Brooklyn, NY, in 2013–2016, a subset of 28 participants who received in-depth qualitative interviews were purposively sampled for a secondary analysis of participants who received an HIV diagnosis and/or medical care while incarcerated. Using an Interpretive Phenomenological Analysis, we found participant's experiences were shaped by longstanding mistrust of the medical establishment. While incarcerated, lack of autonomy, substandard medical care, and poor social support exacerbated medical mistrust and avoidance of HIV medical care long after release. Engagement in HIV medical care and treatment were also impacted by a dynamic interplay of factors including substance use, prolonged periods of denial, poverty, and repeated bouts of incarceration. Given that experiences of HIV diagnosis and medical care while incarcerated have long-ranging, adverse effects, we argue that a better understanding of the ways in which PLWH of color experience HIV diagnosis and medical care while incarcerated may serve to inform intervention efforts within correctional institutions to improve HIV health outcomes.